Long-acting reversible contraceptives effects in abnormal uterine bleeding, a review of the physiology and management. (March 2022) - Castillo, Karina; Zambrano, Kevin; Barba, Diego; Robayo, Paola; Sanon, Serena; Caicedo, Andres; Jijon Chiriboga, Alfredo Jose
Highlights: Intrauterine devices and subdermal contraceptive implants cause abnormal bleeding. Hormonal and copper-based intrauterine devices induce different pathways of bleeding. Abnormal uterine bleeding is a frequent cause of discontinuation among patients. New and different approaches exist to ameliorate abnormal uterine bleeding. Abstract: Around two-thirds of women who are of reproductive age use some type of contraception. Two of the most effective long-acting reversible contraceptives (LARC) are the intrauterine device (IUD) and the subdermal contraceptive implant (SCI). Despite their effectiveness, women often report abnormal uterine bleeding as the reason for discontinuation. In this review, we analyze key aspects regarding the mechanisms of action of IUDs (both copper-containing and levonorgestrel-releasing) and SCIs, as well as how they change the intrauterine environment in order to provide effective contraception at a physiological level. Additionally, we introduce the pathophysiology of different types of abnormal intrauterine bleeding provoked by the mentioned LARCs. These three contraceptive methods work in diverse ways, thus, the etiology of abnormal uterine bleeding is different and multifactorial according to each LARC. This review intends to provide information in order to better our understanding of bleeding induced by these contraceptive methods, as well as introduce current and potential new therapies. Furthermore, this review intends to provide updated and concise information that could be available firsthand not only to health care providers but scientists who are innovating and revolutionizing this field. In 2013, the American College of Obstetricians and Gynecologists published a management of abnormal uterine bleeding, however, there is limited updated data regarding the physiology and pathophysiology of abnormal uterine bleeding and its treatment based on different LARCs (hormonal and non-hormonal).